If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -14 + -2x = 5x + 10 Reorder the terms: -14 + -2x = 10 + 5x Solving -14 + -2x = 10 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -14 + -2x + -5x = 10 + 5x + -5x Combine like terms: -2x + -5x = -7x -14 + -7x = 10 + 5x + -5x Combine like terms: 5x + -5x = 0 -14 + -7x = 10 + 0 -14 + -7x = 10 Add '14' to each side of the equation. -14 + 14 + -7x = 10 + 14 Combine like terms: -14 + 14 = 0 0 + -7x = 10 + 14 -7x = 10 + 14 Combine like terms: 10 + 14 = 24 -7x = 24 Divide each side by '-7'. x = -3.428571429 Simplifying x = -3.428571429
| 21.27=4g+3.95 | | a^2+44=b^3 | | 1.26g-6=0.93 | | x^2y-9+3x=x^2y+5 | | 3x+4-5x=5x-10-5x | | 9x-8=126 | | 3x+17x-4=5(4x+3) | | 98+7=s | | 2.875+2T=3.125 | | y=mx+12 | | -7w+15=1 | | Y-7=-6y | | 1x+2=-3x+9 | | 2-7m=-75 | | 3x-c+8+5x-2=10 | | 2-7m=-73 | | 4x^3-20x^2+4x+300=0 | | 6(1x-6)+6=8x-8 | | -16+2x=-6x+32 | | -15x+24y=500 | | -12-9x=53 | | b(3)=21 | | (6x^4-x^3-3x^2+20)+(10x^3-4x^2+9)= | | 2x-42=x | | 6sq^2(3)+4=x | | 4x^2+9y^2=13 | | 12x-3(2x-4)=3x-9 | | y/2+4=-9 | | 5x+8=5x-5 | | 9-j=72 | | X-100=100 | | 38=a-8 |